2006
DOI: 10.1292/jvms.68.543
|View full text |Cite
|
Sign up to set email alerts
|

DNA Sequence Analysis of Glycoprotein G Gene of Bovie Ephemeral Fever Virus and Development of a Double Oil Emulsion Vaccine against Bovine Ephemeral Fever

Abstract: ABSTRACT. The surface glycoprotein G is considered as the major neutralizing and protective antigen of bovine ephemeral fever virus (BEFV). Comparison of the deduced amino acid sequence of G protein of BEFV isolates during the period 1984-2004 outbreaks in Taiwan showed amino acid substitutions in the neutralizing epitopes. All the isolates differ markedly in the neutralizing epitope at the same amino acid positions compared to the currently available killed vaccine strain (Tn73). Tn88128 strain isolated in 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…It has been confirmed that the G1 protein is specific to BEFV and only reacts with the anti-BEFV neutralising antibodies (Yin & Liu, 1997;Hsieh et al, 2006). The expressed G1 protein in a prokaryotic system, E. coli, had appropriate reaction activity and specificity with an anti-BEFV serum in immunoblot analysis (Zheng et al, 2007a;Beygi Nassiri et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…It has been confirmed that the G1 protein is specific to BEFV and only reacts with the anti-BEFV neutralising antibodies (Yin & Liu, 1997;Hsieh et al, 2006). The expressed G1 protein in a prokaryotic system, E. coli, had appropriate reaction activity and specificity with an anti-BEFV serum in immunoblot analysis (Zheng et al, 2007a;Beygi Nassiri et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Our RT-PCR results support others [28] in the belief that RT-PCR is a superior test for the provision of rapid and specific data for BEFV detection. The conventional RT-PCR is sensitive, specific and rapid test for detection of BEFV in clinical samples [29], moreover we found the RT-PCR assay to be useful for testing RNA samples extracted from peripheral blood mononuclear cells and so it could be an important tool for the screening of BEF infection [30].…”
Section: Discussionmentioning
confidence: 98%
“…The Bovine Ephemeral Fever (BEF; also referred to as "Three-day sickness", "Bovine enzootic fever", "Dengue fever of cattle", "Lazy man's disease" or "Stiffsiekte") is caused by the Bovine Ephemeral Fever Virus (BEFV) of the genus Ephemerovirus of the family Rhabdoviridae (Della-Porta and Brown, 1979;Hsieh et al, 2005;St. George, 1990;Walker et al, 1991;Hamblin, 2008).…”
Section: Ephemeral Fevermentioning
confidence: 99%
“…Virus particles are bullet shaped, enveloped with a length of on average 145 nm and a diameter of 70 nm with not completely parallel sides as well as an inner capsid (Holmes and Doherty, 1970). Five structural proteins are encoded by the negative-sense single stranded RNA (-ssRNA) including a surface protein G (Hsieh et al, 2005) and a non-structural protein (NS) (Hamblin, 2008). Walker et al (1991) found another protein with an unsolved function, which was detected in infected cells but not in virions.…”
Section: Ephemeral Fevermentioning
confidence: 99%
See 1 more Smart Citation